Practical financial economics : a new science - Murphy, Austin, 1956- (Praeger, 2003)
The recent stock market bubble of the late 1990s and subsequent crash has made people more aware of the need to conduct practical financial analysis. Practical financial economics, i.e., the application of financial theory to practical financial analysis, is explained here with respect to a number of different topics, with a focus on valuation. Largely normative (instead of being theoretical, empirical, or descriptive, as most academic work seems to be), yet solidly grounded in theory (instead of being ad hoc, as much purely practitioner work seems to be), this book represents a collection of.